Influences Upon Organizational Ethical Subclimates: A Replication Study of a Single Firm at Two Points in Time - Weber, James (Journal of business ethics, 2002)
This research replicates Weber's 1995 study of a large financial services firm that found that ethical subclimates exist within multi-departmental organizations, are influenced by the function of the department and the stakeholders served, and are relatively stable over time. Relying upon theoretical models developed by Thompson (1967) and Victor and Cullen (1998), hypotheses are developed that predict the ethical subclimate decision-making dimensions and type for diverse departments within a large steel manufacturing firm and that these ethical subclimate types will be stable across the two periods of time when the data were collected. Employees were surveyed in 1995 and again in 1999 using Victor and Cullen's Ethical Climate Questionnaire. Response rates of 88 and 94 percent were achieved. Contrary to Weber's findings, our results imply that, in both samples, ethical subclimates may be determined by the strength of an organization's overall ethical climate, rather than the department's function. However, we did find support for Weber's earlier contention that these subclimates are relatively stable. Our results also suggest that differences may exist across industries, that is when comparing a large steel manufacturer, as we did in our study, with a large financial services organization, as Weber did in his 1995 study.